Generation of ionospheric scintillation maps over Southern China based on Kriging method. Issue 12 (15th June 2020) - Geng, Wei; Huang, Wengeng; Liu, Guoqi; Aa, Ercha; Liu, Siqing; Chen, Yanhong; Luo, Binxian
Highlights: A modeling method of real-time ionospheric scintillation maps are presented. Comparisons indicate that maps are valid, showing better accuracy than GISM. The maps can be considered as a tool to monitor and warn regional scintillation activities. Abstract: Trans-ionospheric communication of radio waves can be affected by ionospheric scintillation which can lead to a complete loss of lock. Scintillation is more prevalent in the ionospheric equatorial anomaly region, and at high latitudes, which is one of the main concerns of space weather services. In this paper, we present the first time a technique to derive a near-real-time ionospheric scintillation index S4 regional mapping based on Kriging method using six low latitude stations in Southern China. The result is compared with the Global Ionospheric Scintillation Propagation Model (GISM) and ionospheric irregularity index represented by the rate of change total electron content index (ROTI) to assess the validation and accuracy of output of Kriging method. It shows that our map could reflect better the regional characteristic and variations of S4 in the Southern China. The lower mean absolute errors and the mean square errors indicate that the results of Kriging method are relatively true and reliable, which could be considered monitoring and warning regional ionospheric scintillation activities under disturbed space weather conditions.